Acne Knowledge of Hispanic Parents of Teenagers with Mild to Moderate Acne. Issue 5 (11th July 2016) - Lopez, Isha; Zapata, Lucio; Sosa, Juan Jesús; Rodgers, Clifford; Ruiz, Maria; Oh, Susan; Hynan, Linda S.; Kimball, Alexa B.; Pandya, Amit G.
Abstract: We performed a cross‐sectional study of Hispanic and non‐Hispanic parents of children with acne using a survey designed to determine their level of awareness of acne and its treatment; 82% of Hispanic parents and 40% of non‐Hispanic parents agreed that a health care provider should treat mild acne (p < 0.001). Hispanic parents of adolescents with acne agreed more frequently than non‐Hispanic parents that children with mild and moderate acne should be taken to a health care provider for treatment, but they tended not to visit health care providers. Future studies should aim to determine the reasons for this discrepancy, after which culturally sensitive educational programs can be developed to address this disparity.